2016
DOI: 10.1002/bjs.10056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on survival in patients undergoing resection of hepatocellular carcinoma

Abstract: Background: The benefit of surgical intervention for cancer should be estimated in relation to the life expectancy of the general population. The aim of this study was to provide a measure of relative survival after hepatectomy for hepatocellular carcinoma (HCC).Methods: Consecutive patients with liver cirrhosis and HCC who underwent hepatectomy were divided into age quartiles for analysis. Short-and mid-term survival rates were used to estimate survival until death for all patients, in relation to age and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 24 publications
2
49
0
Order By: Relevance
“…For a more comprehensive interpretation of the potential benefit of surgery on elderly patients survival, we compared the life expectancy of the normal Italian population with our cohort of HCCbearing patients who underwent an operation with radical intent, as recently suggested by others. 46 The years of potential life lost (PYLL) estimates how many median years a person had lost since his premature death because of cancer, 23 Several study limitations should be acknowledged. Given the retrospective nature of the study, the major bias of our study is the impossibility to retrace "a posteriori" patient selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…For a more comprehensive interpretation of the potential benefit of surgery on elderly patients survival, we compared the life expectancy of the normal Italian population with our cohort of HCCbearing patients who underwent an operation with radical intent, as recently suggested by others. 46 The years of potential life lost (PYLL) estimates how many median years a person had lost since his premature death because of cancer, 23 Several study limitations should be acknowledged. Given the retrospective nature of the study, the major bias of our study is the impossibility to retrace "a posteriori" patient selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Following the same line of reasoning, a variable age threshold beyond which the net benefit for HCC patients does not justify LT over resection or ablation seems questionable, at least until a transplantation‐ versus nontransplantation‐related benefit comparison is adjusted on reference cohorts derived from the general population matched by sex, age, and years of diagnosis. It is worth noting that within the context of patient benefit, both the absolute number of years of life gained and years of life lost with respect to life span (i.e., relative survival) should be considered when assessing the efficacy of surgical therapies offered to older patients …”
Section: Selection and Allocation Principles Reconciled: Has The Circmentioning
confidence: 99%
“…It is worth noting that within the context of patient benefit, both the absolute number of years of life gained and years of life lost with respect to life span (i.e., relative survival) should be considered when assessing the efficacy of surgical therapies offered to older patients. (37) Conversely, a more realistic wait time and priority score based on assumptions shown in Table 2 could silence both the utilitarian and urgency aims while including patients and societal perspectives-a process that seems essential to improve the flexibility of the transplantation system in HCC with respect to noncancer indications.…”
Section: System Solidity and Flexibility Should Be Reinforcedmentioning
confidence: 99%
“…[3032] Furthermore, some studies showed that the elderly patients with HCC possibly had a better OS and/or RFS than that of the younger patients. [33,34] Our modeling also identified the age of < 60 years as an independent predictor of poor long-term survival.…”
Section: Discussionmentioning
confidence: 69%